Use of Shotgun Metagenomics to Assess the Microbial Diversity and Hydrocarbons Degrading Functions of Auto-Mechanic Workshops Soils Polluted with Gasoline and Diesel Fuel - Emerance Jessica Claire D’Assise Goma-Tchimbakala; Ilaria Pietrini; Joseph Goma-Tchimbakala; Stefano Paolo Corgnati (Microorganisms, 2023)
Bioaugmentation is a valuable technique for oil recovery. This study investigates the composition and functions of microbial communities in gasoline- and diesel-contaminated soils of garages Matoko (SGM) and Guy et Paul (SGP) originating from auto mechanic workshops as well as the concentration of soil enzymes β-glucosidase, β-glucosaminidase, and acid phosphatase. The work aimed to evaluate the presence of petroleum-hydrocarbon-degrading bacteria for the development of foreseen bioremediation of oil-contaminated soils. Microbial diversity, as given by shotgun metagenomics, indicated the presence of 16 classes, among which Actinobacteria and Gammaproteobacteria dominated, as well as more than 50 families, including the dominant Gordoniaceae (26.63%) in SGM and Pseudomonadaceae (57.89%) in SGP. The dominant bacterial genera in the two soils were, respectively, Gordonia (26.7%) and Pseudomonas (57.9%). The exploration of the bacterial metabolic abilities using HUMANn2 allowed to detect genes and pathways involved in alkanes and aromatic hydrocarbons in the two contaminated soils. Furthermore, enzymes β-glucosidase, β-glucosaminidase, and acid phosphatase were found in high concentrations ranging between 90.27 ± 5.3 and 804.17 ± 20.5 µg pN/g soil/h, which indicated active microbial metabolism. The high diversity of microorganisms with a hydrocarbon degradation genetic package revealed that the bacteria inhabiting the two soils are likely good candidates for the bioaugmentation of oil-contaminated soils.